Asymmetric Alkyl-Alkyl Cross-Coupling Enabled by Ni-Catalyzed Cross-Hydrodimerization of Enamides with Unactivated Alkenes - Yang, Peng-Fei; Zhao, Han-Tong; Shu, Wei (Synlett, 2024)
Saturated stereogenic centers containing C(sp3)–C(sp3) bonds comprise a major portion of organic molecules. Over the past decades, transition-metal-catalyzed asymmetric C(sp3)–C(sp3) cross-coupling has evolved into an efficient strategy for constructing such stereogenic centers. However, reaction modes to build asymmetric C(sp3)–C(sp3) bonds remain limited. Herein, a nickel-catalyzed enantioselective cross-hydrodimerization between distinct alkenes to enable the enantioselective construction of alkyl–alkyl bonds has been developed. In this reaction mode, N-acyl enamines (enamides) and unactivated alkenes undergo oxidative enantioselective cross-hydrodimerization with excellent levels of chemo- and head-to-tail regioselectivity to give enantioenriched N-acyl α-branched amines by forging the C(sp3)–C(sp3) bond with control of the enantioselectivity. The presence of both reducing and oxidizing reagents in the reaction allows the use of alkenes as sole precursors to forge enantioselective C(sp3)–C(sp3) bonds, representing a new reaction mode for asymmetric alkyl–alkyl cross-coupling. The asymmetric cross-hydrodimerization between distinct alkenes provides a new strategy for constructing saturated stereogenic centers containing C(sp3)–C(sp3) bonds.
Keywords: asymmetric hydrodimerization of alkenes; asymmetric alkyl–alkyl coupling; nickel catalysis; saturated stereogenic centers; alkyl electrophile free